Novel Synthesis of Sensitive Cu-ZnO Nanorod–Based Sensor for Hydrogen Peroxide Sensing - Arsalan, Muhammad; Saddique, Imram; Baoji, Miao; Awais, Azka; Khan, Ilyas; Shamseldin, Mohamed A.; Mehrez, Sadok (Frontiers in Chemistry, 2022)
We aimed to synthesize sensitive electrochemical sensors for hydrogen peroxide sensing by using zinc oxide nanorods grown on a fluorine-doped tin oxide electrode by using the facial hydrothermal method. It was essential to keep the surface morphology of the material (nanorods structure); due to its large surface area, the concerned material has enhanced detection ability toward the analyte. The work presents a non-enzymatic H2O2 sensor using vertically grown zinc oxide nanorods on the electrode (FTO) surfaces with Cu nanoparticles deposited on zinc oxide nanorods to enhance the activity. Scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), energy-dispersive X-Ray (EDX), X-ray diffraction (XRD), and electrochemical methods were used to characterize copper–zinc oxide nanorods. In addition to the high surface area, the hexagonal Cu-ZnO nanorods exhibited enhanced electrochemical features of H2O2 oxidation. Nanorods made from Cu-ZnO exhibit highly efficient sensitivity of 3415 μAmM−1cm−2 low detection limits (LODs) of 0.16 μM and extremely wide linear ranges (0.001–11 mM). In addition, copper-zinc oxide nanorods demonstrated decent reproducibility, repeatability, stability, and selectivity after being used for H2O2 sensing in water samples with an RSD value of 3.83%. Cu nanoparticles decorated on ZnO nanorods demonstrate excellent potential for the detection of hydrogen peroxide, providing a new way to prepare hydrogen peroxide detecting devices.